2022
DOI: 10.1002/exp.20210038
|View full text |Cite
|
Sign up to set email alerts
|

Role of bioaerosol in virus transmission and material‐based countermeasures

Abstract: Respiratory pathogens transmit primarily through particles such as droplets and aerosols. Although often overlooked, the resuspension of settled droplets is also a key facilitator of disease transmission. In this review, we discuss the three main mechanisms of aerosol generation: direct generation such as coughing and sneezing, indirect generation such as medical procedures, and resuspension of settled droplets and aerosols. The size of particles and environmental factors influence their airborne lifetime and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 140 publications
0
5
0
Order By: Relevance
“…The aerosol pathway is a critical way of spreading viruses, especially for highly transmittable respiratory infections such as H1N1 [8], which is capable of changing the cluster size of the virus according to temperature, atmospheric pH, and hygroscopicity that can directly influence the movement of virus particles in the nasopharyngeal passages [230]. Furthermore, H1N1 can shape clusters with the size of 400 nm and then they grow larger in the saliva to form aerosols the size of 0.7 mm to 6 µm, which can easily spread in the environment by the change in airflow trajectory during sneezing and coughing [231].…”
Section: Nanofibrous Air Filters and Face Masksmentioning
confidence: 99%
See 2 more Smart Citations
“…The aerosol pathway is a critical way of spreading viruses, especially for highly transmittable respiratory infections such as H1N1 [8], which is capable of changing the cluster size of the virus according to temperature, atmospheric pH, and hygroscopicity that can directly influence the movement of virus particles in the nasopharyngeal passages [230]. Furthermore, H1N1 can shape clusters with the size of 400 nm and then they grow larger in the saliva to form aerosols the size of 0.7 mm to 6 µm, which can easily spread in the environment by the change in airflow trajectory during sneezing and coughing [231].…”
Section: Nanofibrous Air Filters and Face Masksmentioning
confidence: 99%
“…Although the severity and mortality of COVID-19 are less than most of other epidemic coronaviruses (i.e., SARS-CoV and MERS-CoV), it is much more transmissive and can be easily spread via the virus-containing droplets originating from sneezing, coughing, exhalation, or by contacting contaminated materials [7]. The aerosol pathway cannot be neglected as the most critical and dominant way of the virus to spread [8]. Even though a majority of the population in developed and developing countries have received vaccines, high mutation rates in the genome of COVID-19 [9] have been leading to emergence of new variants (i.e., Omicron [10]) that can cause a whole different type of symptoms, sometimes more severe and long-lasting complications, beyond the immunizing power of the vaccines which were introduced so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We contend that the sub-optimal clinical efficacy of previous chemoprophylactic nasal sprays can be attributed, at least in part, to their dependence on a single mode of action, which usually entails either pathogen neutralization or the creation of a physical barrier to hinder pathogen entry through the nasal lining. Furthermore, since pathogens gain access to the nasal cavity through large respiratory droplets( 24 ), an optimal prophylactic strategy should also prioritize the effective capture of these droplets laden with pathogens. This necessitates preventing them from bouncing off, a factor that has not been addressed in prior approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Hyytiainen et al (2018) [11] reported that bacteria and fungal levels were 8 to 21 fold higher in the breathing zone of a crawling infant robot compared to those measured in the breathing zone of an adult. Numerous other investigations on the resuspension of bioaerosols, primarily bacteria and fungi, have been conducted within the last two decades [9,[12][13][14][15][16][17][18]. However, the resuspension of viruses or particles containing viruses via human activity has not been studied experimentally.…”
Section: Introductionmentioning
confidence: 99%